Gambaran Kejadian Dermatitis Kontak Pada Pekerja Produksi Busa Spons di PT. Esterindo - Djap Hadi Susanto (Jurnal MedScientiae, 2022)
Contact dermatitis is a major health problem of skin disease for workers who have a history contact with chemicals or irritants. This disease can usually be found in industry, plantations or agriculture. This research is a descriptive study with a method of cross-sectional study. The total sample of subjects obtained was 76 subjects which were explored through interviews, observation, questionnaires and diagnosed from a doctor. Based on the results, workers with contact dermatitis were 14 workers, 18,4%. The most common groups who got contact dermatitis were the age group of 40-49 years (31,8%), women (15,7%), pasting sponge group (33,3%), average working period in 2 years and a half month, in average 5 days of working and an average of 7 hours working in a day. The total workers who has contact dermatitis in Esterindo factory are 14 workers (18,4%). The incidence of contact dermatitis in Esterindo factory could be affected from discipline of workers in the use of personal protective equipment, characteristics and different types of activities in each worker, medical history and history of skin diseases.